2018
DOI: 10.1002/ecs2.2415
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between invader abundance and impact

Abstract: The impacts of invasive species generally increase with their abundance, but the form of invader abundance–impact relationships remain poorly described. We highlight the utility of abundance–impact curves for three questions. First, abundance–impact relationships can clarify whether prevention and management should focus on the species likely to become abundant or those likely to cause large impacts per individual. Second, comparing abundance–impact relationships between native and exotic species can reveal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 73 publications
(143 reference statements)
6
94
0
Order By: Relevance
“…Moreover, we found that native overstory cover varied negatively with time since invasion, consistent with an impact scenario wherein local-scale decrements in native abundance build over time as a function of invader abundance (Dost al et al 2013, Sofaer et al 2018. First, we minimized background variation in conditions by sampling plant abundance in uninvaded plots located proximal to invaded plots at each study site.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Moreover, we found that native overstory cover varied negatively with time since invasion, consistent with an impact scenario wherein local-scale decrements in native abundance build over time as a function of invader abundance (Dost al et al 2013, Sofaer et al 2018. First, we minimized background variation in conditions by sampling plant abundance in uninvaded plots located proximal to invaded plots at each study site.…”
Section: Discussionsupporting
confidence: 71%
“…Populations of potent invaders are generally assumed to increase over time ), but population growth may eventually attenuate due to many factors (Ricciardi et al 2013, Yelenik and D'Antonio 2013. This pattern is in line with theory linking local-scale competitive effects to biomass (Parker et al 1999, Pearson et al 2016, Sofaer et al 2018. 2), with some weak evidence for an eventual slowing of population growth (Appendix S2: Table S3).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is apparent that neither species richness nor traits such as height, clonality, or perennial life form show any suppression or exhibit even a positive relation to the dominants’ cover, until some threshold value of its dominance is reached, and then the relationships change to negative (see also Sofaer et al. ).…”
Section: Discussionmentioning
confidence: 99%